2018
DOI: 10.1021/acsabm.8b00398
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Chronocoulometric Detection of miRNA at Screen-Printed Electrodes Modified by Gold-Decorated MoS2Nanosheets

Abstract: Developing novel simple and ultrasensitive strategies for detecting microRNAs (miRNAs) is highly desirable because of their association with early cancer diagnostic and prognostic processes. Here a new chronocoulometric sensor, based on semiconducting 2H MoS2 nanosheets (MoS2 NSs) decorated with a controlled density of monodispersed small gold nanoparticles (AuNPs@MoS2), was fabricated via electrodeposition, for the highly sensitive detection of miRNA-21. The size and interparticle spacing of AuNPs were optimi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Hybridization efficiency (HE%) is calculated as evidence of the probe and miRNA hybridization efficacy in order to determine optimum conditions [49].…”
Section: Voltammetric Detection Of Mirna-155 and Mirna-21 By A Aunp/rgo-modified Paper Electrodementioning
confidence: 99%
“…Hybridization efficiency (HE%) is calculated as evidence of the probe and miRNA hybridization efficacy in order to determine optimum conditions [49].…”
Section: Voltammetric Detection Of Mirna-155 and Mirna-21 By A Aunp/rgo-modified Paper Electrodementioning
confidence: 99%
“…Similarly, a 1.8 fold increase at R ct was observed in the presence of hybridization of the DNA probe with the wDNA target. According to the literature [50], the hybridization efficiency (HE%) provides information about the hybridization effectiveness. As a result, the hybridization efficiency (HE%) of our assay was also calculated and shown in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the impedimetric detection of the FV Leiden mutation was performed in contribution of the ZNA probe which resulted in a relatively shorter time (i.e., 30 min) and selectively in comparison to earlier studies in the literature without using any type of labeled probe [23,24,25,36,37,38,50,51,52,53,54,55,56,57]. Some of these studies related to the electrochemical detection of FV Leiden mutation was presented in Table S6.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of SPCE-based miRNA-specic biosensors have used single channel electrodes to detect singular miRNA species. [27][28][29] These include a dual working surface system, 30 and a method using DNA nanostructures on an array of 16 gold electrodes. 31 By contrast, Erdem et al demonstrated multiplexed miRNA detection using a system containing 16 active surfaces with shared counter and reference electrodes, 32 and in one case used this set up to detect multiple miRNA species simultaneously.…”
Section: Sensor Designmentioning
confidence: 99%